Decision difficulties of long‐term‐care facility nurses in transferring residents to the emergency department: A cross‐sectional nationwide study. (23rd February 2021) - Chen, Bor‐An; Lai, Fu‐Chih; Tsao, Lee‐Ing; Chien, Hui‐Hui; Chen, Chun‐Fu; Jeng, Chii
Abstract: Aims: To examine the level of decision difficulties of long‐term‐care facility (LTCF) nurses when transferring residents to the emergency department (ED) and associated influencing factors. Design: A cross‐sectional nationwide study. Methods: The LTCFs were selected through random stratified sampling across the whole Taiwan during February 2018 to January 2019. LTCF nurses who met the selection criteria were invited to participate with two or three nurses selected from each LTCF. The Patient Transfer Decision Difficulty Scale (PTDDS) was used to measure the level of difficulty in making decisions related to the transfer of residents to the ED. Data were collected by mailing the questionnaires and asking the nurses to return the completed form in 2 weeks. Data were analysed using simple linear regression and multiple regression with stepwise methods. Results: In total, 618 valid questionnaires with an 85.32% response rate from 319 LTCFs were used for the data analysis. Decision difficulties that LTCF nurses experienced were moderate, the nursing personnel‐bed ratio, LTCF professional training and basic life support training were predictive factors of the level of difficulty experience (scores of PTDDS) for the LTCF nurse ( F = 6.81, p < .001). Conclusions: Enhancing emergency training in LTCF can improve nurses' decision‐making ability to refer LTCF residents to emergency treatment. Impact: What problem did the study address? The study addressed the difficult decision LTCF nurses may experience when transferring a resident to the emergency department. What were the main findings? All LTCF nurses faced a moderate level of difficulty in decision‐making. 'Transfer timing' was most often considered in the decision‐making process when a resident was transferred to the ED. Where and on whom will the research have impact? Results of this study have considerable reference value for LTCF managers and nurses in the decision‐making ability and suitability of transferring residents for emergency treatment.